Environmental factors associated with disease flare in juvenile and adult dermatomyositis. (21st April 2017) - Mamyrova, Gulnara; Rider, Lisa G.; Ehrlich, Alison; Jones, Olcay; Pachman, Lauren M.; Nickeson, Robert; Criscone-Schreiber, Lisa G.; Jung, Lawrence K.; Miller, Frederick W.; Katz, James D.
Abstract: Objective. The aim was to assess environmental factors associated with disease flare in juvenile and adult dermatomyositis (DM). Methods. An online survey of DM patients from the USA and Canada examined smoking, sun exposure, infections, medications, vaccines, stressful life events and physical activity during the 6 months before flares, or in the past 6 months in patients without flares. Differences were evaluated by χ 2 and Fisher's exact tests, and significant univariable results were examined in multivariable logistic regression. Residential locations before flare were correlated with the National Weather Service UV index. Results. Of 210 participants (164 juvenile and 46 adult DM), 134 (63.8%) experienced a disease flare within 2 years of the survey. Subjects more often reported disease flare after sun exposure [odds ratio (OR) = 2.0, P = 0.03], although use of photoprotective measures did not differ between those with and without flare. Urinary tract infections (OR = 16.4, P = 0.005) and gastroenteritis (OR = 3.2, P = 0.04) were more frequent in the preceding 6 months in those who flared. Subjects who flared recently used NSAIDS (OR = 3.0, P = 0.0003), blood pressure medicines (OR = 3.5, P = 0.049) or medication for depression or mood changes (OR = 12.9, P = 0.015). Moving to a new house (OR = 10.3, P = 0.053) was more common in those who flared. Only sun exposure (OR = 2.2) and NSAIDs (OR = 1.9) were significant factors in multivariable analysis. Conclusion. Certain classes of environmental agents that have been associated with the initiation of DM, including sun exposure and medications, may also play a role in disease flares.